Differentiation of Electricity Prices: Role of Space and Institutions - Olga Valeryevna Dyomina; Pavel Aleksandrovich Minakir (Prostranstvennaâ Èkonomika, 2016)
The article discusses the empirical material based features of the functioning of spatially distributed power systems and the relevant markets in the «big» countries: Russia, USA, Canada and China. The following hypothesis are tested: 1 - inter-territorial differentiation of electricity prices is not an exclusive phenomenon of the industrial market failure in Russia, but describes the common pattern of the electricity market in the «big» countries; 2 - the formation of the institute of price discrimination of power consumers is caused by objective reasons (it has an objective character). It is shown that the objective differentiation of geographic conditions of the electrical energy generation, distribution and consumption in the «big» countries determines the presence of markets multiplicity, accompanied by prices levels multiplicity caused by multiple levels of production cost and electricity transmission, which is contrary to the principles of market competitiveness and social equity. The resolution of this contradiction in all countries above breeds preservation and even the strengthening of state electricity price regulation in the form of cross-subsidization. Cross-subsidization leads to price discrimination of consumers, forms of which vary depending on the institutional conditions that determine the specific mechanism and purpose of such discrimination: in Russia and in China - between groups of consumers; in the United States - between customers of different states; in Canada - existence in most provinces of vertically integrated companies which suggests the presence of price discrimination of electricity consumers